AGGREGATION CRITERIA FOR SURFACE HEAT BALANCES IN A HETEROGENEOUS AREA BASED ON A LINEAR MODEL - Nakaegawa T.; Oki T.; Musiake K. (My University, 2001)
The present study treats the aggregation of the heterogeneity of the surface heat fluxes. The aggregation criteria proposed here are used to evaluate the aggregation error and to calculate the maximum values of the statistics of the distributing parameters with a given tolerance error. The intrapatch scale distribution of the surface flux bulk transfer coefficient can be aggregated within a tolerance error of 5 W/m2 using the mean parameter method (MPM) in all cases, but the evaporation efficiency cannot be aggregated using MPM in some cases. However, aggregation is possible even when the moment method of second-order (MM2) is applied. The interpatch scale heterogeneity at an area constituted of different land cover types can be aggregated with good accuracy using MM2. This result reveals that aggregation using the dominant land cover method (DLM) and MPM could result in a significant error of more than 40 W/m2.
Keywords: AGGREGATION; SURFACE HEAT BALANCE; HETEROGENEITY; MOMENT METHOD; TOLERANCE ERROR; AGGREGATION CRITERIA